Classic Papers in Orthopaedics - Banaszkiewicz, Paul A.; Kader, Deiary F. (Springer London : Imprint: Springer, 2014)
The book categorizes articles by field of research to include studies on the hip and knee arthroplasty, sports medicine and arthroscopy, paediatric orthopaedics foot and ankle, spine, hand and upper extremity, trauma/fracture healing, oncology and basic science articles (stem cell, bone tissue, ligament, tendon tissue and implants).   Classic Papers in Orthopaedics assembles a distinguished team of contributors to identify, analyze and bring together in a single volume the most important articles from a broad range of publications that have become recognized as the defining articles in orthopaedics. It is a unique reference providing a single source for reviewing the most important papers in the discipline. It also provides a critical analysis of the strengths, weaknesses and the impact each paper has had on the development of orthopaedics and is therefore essential reading for all practicing orthopaedic surgeons, orthopaedic trainees sitting higher level exams, and all involved in research and clinical practice in the field of orthopaedics.